Physiological responses of four soybean varieties and their effect to the yield in several saturated soil culture modification - Toyip; MUNIF GHULAMAHDI; DIDY SOPANDIE; SANDRA A AZIZ; ATANG SUTANDI; M. YANUAR J. PURWANTO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Toyip, Ghulamahdi M, Sopandie D, Aziz SA, Sutandi A, Purwanto MYJ. 2019. Physiological responses of four soybean varieties and their effect to the yield in several saturated soil culture modification. Biodiversitas 20: 2266-2272. This study aimed to evaluate the production and physiological response of four soybean varieties in saturated soil culture (SSC), compared to conventional dry culture on tidal swamp soil growing media. Four popular varieties in Indonesia, namely Anjasmoro, Grobogan, Tanggamus and Malika, were planted on undisturbed intact tidal swamp soil from Jambi from November 2016 to March 2017 at Bogor. Randomized completely block design with two factors applied in this work, i.e. 4 varieties namely Anjasmoro, Grobogan, Tanggamus and Malika; and 9 culture methods such as dry culture as control of no SSC (i), 1 months SSC (ii), 1.5 months SSC (iii), 2 months SSC (iv), continuous SSC (v), 1 months SSC with water improvement (vi), 1.5 months SSC with water improvement (vii), 2 months SSC with water improvement (viii), and continuous SSC with water improvement (ix). The results showed that (i) pod production per plant was significantly affected by the interaction of both factors; (ii) different varieties lead to significant different of physiological response, i.e. photosynthetic rate, transpiration rate, stomatal conductance and water use efficiency; (iii) the variation of culture methods only showed a significant effect on photosynthetic rate, i.e. saturated soil culture with water improvement (SSC WI) showed 48% and 18% higher photosynthetic rate than dry culture and regular SSC methods, respectively. Pod production was positively correlated to photosynthetic rates and water use efficiency; and negatively correlated to transpiration and stomatal conductance. The highest number of pod production per plant was achieved by Malika variety that planted in 2 months SSC WI.